Exploring extreme burnout in public hospital resident physicians: identification and mitigation of risk factors through effective coping strategies - Rodríguez, Marvin (Revista Acciones Médicas, 2024)
Burnout syndrome (BS) is a work-related concern that affects physicians, causing significant repercussions on mental health, quality of life, work performance, and service delivery. The aim of this study was to review the published scientific evidence on BS, its risk factors, and effective coping strategies in public hospital resident physicians. Using a qualitative approach, using the systematic literature review methodology, an exhaustive search of articles was conducted in various databases (SCOPUS, Google Scholar, Scielo, Dialnet, and Redalyc), finding 1165 articles. After a review process, 16 articles were selected that met specific inclusion criteria, such as being original research, related to the topic, complete, and in Spanish and English, with a time period of 2021 to 2023, repeated, incomplete, and restricted articles were discarded. The results reveal a high prevalence and consistency of BS in residents, affecting more than half, especially those in higher years. Emotional exhaustion is highlighted as the most affected sub-scale. Predisposing factors include high workload and academic load, exhausting shifts, and situations of abuse, mistreatment, and harassment. The need to implement measures at the individual, organizational, and policy levels is emphasized, which could be effective in preventing and managing BS. In conclusion, BS in resident physicians is attributed to chronic exposure to stressful factors, highlighting the importance of addressing this problem comprehensively in public hospitals through effective interventions.
Keywords: burnout syndrome; extreme exhaustion; medical specialties; public hospitals; resident doctors